Analisis Laporan Keuangan Segmen dan Laporan Keuangan Interim pada PT Semen Indonesia (Persero) Tbk Tahun 2015–2019 - Halimah, Ahaddiana Fitriani (Jurnal KIAFE, 2025)
This study analyzes the conformity of segment financial reporting and interim financial reporting at PT Semen Indonesia (Persero) Tbk with PSAK No. 5 and PSAK No. 3 during the 2015–2019 period. The study employs a descriptive case-study approach using secondary data obtained from the company’s annual and interim financial reports. Quantitative analysis was conducted through the 10% revenue, asset, and profit-or-loss threshold tests, the additional-segment test, and the dominant-segment test. Qualitative analysis was performed by comparing the company’s segment and interim financial disclosures with the requirements of PSAK No. 5 and PSAK No. 3. The results show that the determination of reportable operating segments in 2015 did not fully comply with PSAK No. 5 because the non-cement production segment failed all three quantitative threshold tests but remained separately reported. In contrast, segment reporting during 2016–2019 complied with PSAK No. 5. No additional reportable segment was required because the disclosed segments represented more than 75% of total external revenue. The cement production segment was identified as the dominant segment throughout the study period. The disclosure of operating-segment information complied with PSAK No. 5, while the interim financial statements included the minimum required components and complied with PSAK No. 3.